IKLAN SEBAGAI FAKTOR PENGGANGGU KENYAMANAN PENGGUNA MEDIA DARING - Siswanta; Maya Sekarwangi; Aris Triharyanto (Fakultas Ekonomi Universitas Yos Soedarso, 2023)
This research explains the attitude of students accessing digital media to advertising impressions on digital media. Primary data collection was carried out by conducting in-depth observations and interviews with informants, and students accessing digital media through smartphones. By using the purposive sampling data snippet technique, the determination of informants is made aware of a number of criteria, namely students who actively access digital media via smartphones, have a sufficient understanding of English, have and are active in social media communication networks, and are active as internet accessors for distance learning purposes. The data from the study showed that not all students who access digital media refused the presence of advertisements. Rejection of ad impressions is based on consideration of the extent to which the appearance of such advertisements interferes with the convenience of the online media communication process. Keywords: Communication Noises; Advertising; Digital Media; Internet.